2018
DOI: 10.1007/s00484-018-1541-3
|View full text |Cite
|
Sign up to set email alerts
|

Hatching delays in great tits and blue tits in response to an extreme cold spell: a long-term study

Abstract: Variation in ambient temperature affects various life stages of organisms. It has been suggested that climate change not only implies higher global temperatures but also more unpredictable weather and more frequent extreme weather events. Temperature has a major influence on the optimal laying-incubation-hatching dates of insectivorous passerines, because it poses energetic constraints and affects the timing of food abundance. We have been studying breeding characteristics of great tits Parus major and blue ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The large temperature drop in 2017 was also recorded in many tit populations (and other bird populations, Shitikov et al 2019) all over the Europe: in Belgium, England, France, Germany, Hungary, the Netherlands, Poland (Figs. 1, 2), Sweden, and others (see Glądalski et al 2018a). The critical period of the temperature drop during the layingincubating period in April of 2017 lasted for about 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The large temperature drop in 2017 was also recorded in many tit populations (and other bird populations, Shitikov et al 2019) all over the Europe: in Belgium, England, France, Germany, Hungary, the Netherlands, Poland (Figs. 1, 2), Sweden, and others (see Glądalski et al 2018a). The critical period of the temperature drop during the layingincubating period in April of 2017 lasted for about 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…There is still little information about how climate change and extreme weather events may influence breeding traits and reproduction parameters in animals (Charmantier et al 2008;Pipoly et al 2013;Charmantier and Gienapp 2014;Glądalski et al 2016Glądalski et al , 2018aMainwaring et al 2017;van de Pol et al 2017;Wingfield et al 2017). Therefore, it was suggested that those extreme weather events may be treated as natural experiments that could shed light on the mechanisms by which birds adjust their breeding characteristics to environmental variability (Jentsch et al 2007;Bailey and van de Pol 2016;Marrot et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…due to loss of some of their actual offspring. If several extreme events occur or an extreme event takes long time in a single breeding season, majority of breeding individuals may die or may not successfully raise offspring which then can have population-level consequences (Møller 2011;Glądalski et al 2018).…”
Section: Introductionmentioning
confidence: 99%